INFLASI, SUKU BUNGA DEPOSITO DAN RETURN PASAR TERHADAP RETURN SAHAM PADA INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI 2006 - 2009 - ELLEN RUSLIATI; SYARAH NURUL FATHONI (Jurnal Bisnis dan Akuntansi, 2011)
This article examines the influence of inflation, interest rates, and market return on stock return in consumer goods industry which is registered in BEI 2006 - 2009. Data obtained from Statistik Ekonomi dan Keuangan Indonesia (SEKI) published by Bank Indonesia, ICMD, and Yahoo Finance Historical Prices. Methods analysis used are descriptive and erificative with panel data regression. The results showed that inflation , deposit rates and market return explain stock return of 68.52 %. Inflation and deposit rates partially have negative effect on stock returns , while market return has positive effect.